Bauran Promosi Pada Dealer Yamaha Tretan Motor Dengan Pendekatan Mixed Methods - Intan Yullia Ningsih; Mohammad Arief (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
This study aims to determine whether the promotional mix consisting of advertising, personal selling, sales promotion, public relations and direct marketing affects purchasing decisions. The research method used in this research is mixed methods, which is a combination of quantitative and qualitative methods. The data collection strategy used sequential explanatory, namely research with two stages. Data analysis used quantitative and qualitative approaches. The results show that in quantitative research all each variable consisting of advertising, personal selling, sales promotion, public relations and direct marketing has a significant effect on purchasing decision variables and this quantitative research is supported by a qualitative approach, namely in the form of a promotional mix applied to dealers. Yamaha Tretan Motor.